Al-qur’an braille sebagai media dakwah kepada penyandang DSN dan untuk meningkatkan literasi Islam - Primi Rohimi; Zahrotun Nufus (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2021)
People with blind sensory disabilities use da’wa media that make it easier to receive da’wa messages. The purpose of this study was to describe the dakwah among people with visually impaired sensory at the Pendowo Kudus Pendowo Pendowo Kudus Social Services for Sensory Disabilities which includes an overview of dakwah; the use of the Braille Qur'an as a medium of dakwah; and the supporting and inhibiting factors. This research is field research that uses a qualitative approach. The process of collecting data using semi-structured interviews, observation, and documentation. This study concludes that dakwah at the Pendowo Kudus Pendowo Netra Sensory Disability Social Service Center includes an invitation to perform obligatory and sunnah worship. The use of the Braille Qur'an as a medium of dakwah begins with teaching Braille Al-Qur'an reading and writing. The supporting factor of the Braille Qur'an as a medium of dakwah is to know the word of God not only through sound but the tactual nature (touchable/touchable and sound) in the Braille Qur'an which is considered appropriate for people with visually impaired persons. The letters in the Braille Qur'an have similarities with the Latin Braille letters so that they are easier to learn. The paper used also has a special standard, so it is not easily damaged. The inhibiting factor in the use of the Braille Qur'an is the determination to learn. The separated form per juz makes it less practical. Purchases of Braille Korans must go through an order because not every store provides Braille Korans. People with blind sensory disabilities who have wet hands can be an obstacle in the learning process. To be able to master reading in the Braille Qur'an, takes quite a long time because the letters and stakes are written separately in the Braille Qur'an.